Kinerja Aparat Dalam Memberikan Pelayanan Administrasi (Studi Pada Kantor Kecamatan Tongauna Kabupaten Konawe) - Yuliana Musin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
Improving the performance of the apparatus is not only pursued through decisions, but through the enhancement of the capacity of the apparatus in providing various materials on the management of administrative services through structural training at various levels. the performance of apparatus in administrative services is not enough to be done only by using indicators inherent in the recipients of services such as the satisfaction of the service users, but in line with the community's need for quality service from the government, then as a public servant who won the trust of the community, must always refer to the satisfaction of the community which is the main purpose in service delivery and continuously make efforts to improve the performance apparatus, thus the authors are interested in conducting research titled "Performance Apparatus in Administration Services". This research was conducted to find out whether the administrative service is in accordance with the expected, then the measurement of the success of administrative services performed by the apparatus through the performance that has been established with the standard of administrative services. In addition, this study was also conducted to determine the factors that affect the performance of officials in performing services that can be seen from the availability of facilities and infrastructure, service procedures, and the ability of employees. This study used a qualitative descriptive approach with data collection obtained from observation, interview and document review. The results of this study indicate that the performance of officials in administrative services in sub-district Tongauna is still not maximized which can be seen from the uncertai settlement guarantee, inadequate facilities and infrastructure, lack of attention and good responses from employees, the lack of employee responsiveness and lack of information given to community regarding service procedures. Researchers suggested that the Government Tongauna Sub-district of Konawe District improves employee performance by training officers, adding facilities and infrastructure as well clarify information on service procedures.